PENGARUH BRAND PREFERENCES TERHADAP CUSTOMER LOYALTY MELALUI KEPUASAN KONSUMEN CHATIME DI SURABAYA - Wike Laurenzia Warrauw (Referensi : Jurnal Ilmu Manajemen dan Akuntansi, 2020)
One of the contemporary drink brands, Chatime has significant regular customers. This Study aims to determine the effect of Brand Preferences on Customer Loyalty Through Customer Satisfaction at Chatime in Surabaya. At least there are several indicators contains in each element that underlines the questionnaire that has been distributed to the target of the researcher. This research was conducted using quantitative methods using the method of calculating the results of the GSCA which the overall results of the indicators were declared valid and reliable. Hypothesis test results indicate that the value estimate on the relationship between customer satisfaction has a positive and significant effect on brand preferences.